Effects of artificial weathering in NR/SBR elastomer blends. (February 2023) - Karekar, Akshay; Schicktanz, Carsten; Tariq, Muhammad; Oßwald, Katja; Reincke, Katrin; Cepus, Valentin; Langer, Beate; Saalwächter, Kay
Highlights: Crosslink densities in the phases of natural rubber (NR) and styrene-butadiene rubber (SBR) blend subjected to weathering are quantified. Contrary to individual rubbers, their phases in the blend are less susceptible to weathering. Blend is better suited for long-term usage. Crosslink densities in the phases of natural rubber (NR) and styrene-butadiene rubber (SBR) blend subjected to weathering are quantified. Contrary to individual rubbers, their phases in the blend are less susceptible to weathering. Blend is better suited for long-term usage. Abstract: Degradation of polymer blends occurs by the constituent phases undergoing distinct chemical changes that depend on their unique chemical structures. This makes predicting and establishing a structure-property relationship for each phase necessary as well as challenging. In this work, the molecular and physical changes occurring in sulfur-cross-linked natural rubber (NR), styrene−butadiene rubber (SBR), and their 50/50 blend subjected to accelerated weathering are analyzed by 1 H nuclear magnetic resonance (NMR) spectroscopy, Fourier-transform infrared (FTIR) spectroscopy, atomic-force microscopy (AFM), and dynamic mechanical thermal analysis (DMTA). NMR transverse relaxation time ( T 2 ) studies suggest the formation of rigid components due to weathering. FTIR and AFM reveal that this is related to the formation of a stiff surface due to chemical modifications, which shows up as an additional thermal transition in the DMTA curves. Low-field double-quantum (DQ) NMR studies of the cross-link density, by the residual dipolar coupling constant ( D res ), of SBR show a continuous increase in its cross-link density over the weathering duration (988 h). In contrast, NR exhibits dominant chain scission reactions resulting in defects, with both materials demonstrating the formation of different chain lengths. During the first 168 h, NR also undergoes modification of sulfur bond lengths, which is also observed in the blend. The blend largely follows an intermediate trend of cross-link densities compared to the two polymers but shows signs of lesser chain modifications than a weighted average of the two polymers. This is confirmed by phase-resolved DQ magic-angle spinning (MAS) NMR experiments whereby the peak-specific D res of the blend was measured to be less modified than that of the individual vulcanizates, thus proving that the blend is more resistant to weathering than its constituent elastomers.